Tree Rings and Observations Suggest No Stable Cycles in Sierra Nevada Cool‐Season Precipitation. Issue 3 (9th March 2021) - Williams, A. P.; Anchukaitis, K. J.; Woodhouse, C. A.; Meko, D. M.; Cook, B. I.; Bolles, K.; Cook, E. R.
Abstract: California's water resources rely heavily on cool‐season (November–March) precipitation in the Sierra Nevada. Interannual variability is highly volatile and seasonal forecasting has little to no skill, making water management particularly challenging. Over 1902–2020, Sierra Nevada cool‐season precipitation totals exhibited significant 2.2‐ and 13–15‐year cycles, accounting for approximately 40% of total variability and perhaps signifying potential as seasonal forecasting tools. However, the underlying climate dynamics are not well understood and it is unclear whether these cycles are stable over the long term. We use tree rings to reconstruct Sierra Nevada cool‐season precipitation back to 1400. The reconstruction is skillful, accounting for 55%–74% of observed variability and capturing the 20th‐century 2.2‐ and 13–15‐year cycles. Prior to 1900, the reconstruction indicates no other century‐long periods of significant spectral power in the 2.2‐ or 13–15‐year bands. The reconstruction does indicate significant cyclicity over other extended periods of several decades or longer, however, with dominant periodicities in the ranges of 2.1–2.7 and 3.5–8 years. The late 1700s through 1800s exhibited the highest‐amplitude cycles in the reconstruction, with periodicities of 2.4 and 5.7–7.4 years. The reconstruction should serve to caution against extrapolating the observed 2.2‐ and 13–15‐year cycles to guide future expectations. On the other hand, observations and the reconstruction suggest that interannual variability of Sierra Nevada cool‐season precipitation is not a purely white noise process and research should aim to diagnose the dynamical drivers of extended periods of cyclicity in this critical natural resource. Key Points: Forty percent of 1902–2020 cool‐season precipitation variability in California's Sierra Nevada range is accounted for by 2.2‐ and 13–15‐year cycles Our novel tree‐ring reconstruction captures these cycles and indicates that they have not been stable features over the past six centuries Extended periods of reconstructed cyclicity nonetheless suggest potentially untapped potential for statistical seasonal forecasting